1993
DOI: 10.1093/oxfordjournals.humrep.a138145
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonographic evaluation of endometrial growth and texture in spontaneous ovulatory cycles—a descriptive study

Abstract: Repeated transvaginal ultrasonographic examinations were performed during spontaneous ovulatory cycles to follow the texture and growth pattern of the endometrium in 23 healthy volunteers. The serum concentrations of oestradiol, progesterone and luteinizing hormone (LH) were measured regularly. The day of the LH peak was designated as day 0. On ultrasound only one thin echogenic line was seen from menstruation to day -7. From days -6 to -1 a change from one to three thin lines was observed together with an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 12 publications
5
45
1
Order By: Relevance
“…12 However, since a correlation between echogenicity and progesterone has not been demonstrated, other factors such as androgen and gonadotropin effects could explain these changes. 13 In our research, all cases who achieved pregnancy had a triple-line pattern of the endometrium on day of HCG. In eight cases, there was gapping between the endometrium and fluid inside, and none of these cases achieved pregnancy.…”
Section: Discussionmentioning
confidence: 54%
“…12 However, since a correlation between echogenicity and progesterone has not been demonstrated, other factors such as androgen and gonadotropin effects could explain these changes. 13 In our research, all cases who achieved pregnancy had a triple-line pattern of the endometrium on day of HCG. In eight cases, there was gapping between the endometrium and fluid inside, and none of these cases achieved pregnancy.…”
Section: Discussionmentioning
confidence: 54%
“…The usefulness of ultrasonography in the endometrial diagnostic has been described earlier, both in natural ovulatory cycles [14] and in therapeutic monitoring [15,16]. Furthermore, it has been shown that the transvaginal technique is superior to the transabdominal technique, because of its better imaging qualities using higher frequencies [8,9,17].…”
Section: Discussionmentioning
confidence: 99%
“…Both machines were equipped with a 5.0-MHz vaginal transducer with a scanning sector of 90° and a focal range of the transducer of 8 cm. Details about the method of examination and measurements were published earlier [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the secretory phase of the menstrual cycle, the endometrium acquires a hyperechogenic morphology that is due to stromal edema, spirilization and secretion of the endometrial glands caused by the action of progesterone (Bassil et al, 2001;Fanchin et al, 2000;Fanchin et al, 2001;Leibovitz et al, 1999). However, since a correlation between echogenicity and progesterone has not been demonstrated (Bakos et al, 1993;Khalife et al, 1992) other factors such as androgen and gonadotropin effects could explain these changes (De Ziegler and Fancin, 1994;Tang and Gurpide, 1993).…”
Section: Endometrial Patternmentioning
confidence: 99%